Molecular epidemiology of nosocomial infections in an intensive care unit: results of a one-year surveillance study (Italian Journal of Public Health, 2005)
Background. Nosocomial infections contribute substantially to increased morbidity, mortality and resourceexpenditure in Intensive Care Units (ICUs).Methods. A one-year prospective surveillance study was performed using epidemiological andmicrobiological methods to quantify the frequency of infections and the antimicrobial usage, microbiologicalenvironmental sampling and molecular typing of clinical and environmental isolates.Results. The frequency of ICU-acquired infections was comparable to other Italian ICUs. Most of theseinfections were caused by few epidemic clones of Pseudomonas aeruginosa, methicillin-resistantStaphylococcus aureus and Acinetobacter baumannii. The survival advantage of these epidemic clones overthe sporadic isolates may be related to the multi-resistant profile of the epidemic clones and to the highusage of some antibiotics in the ICU. Hand contamination of ICU personnel is a likely factor for disseminationof epidemic clones within the ICU.Conclusions. The integrated surveillance approach described in this study is able to clarify the complexepidemiology of ICU-acquired infections and can provide important cues for prevention and controlactivities.
Keywords: molecular epidemiology; surveillance; nosocomial infections; intensive care units